ANALISIS POTENSI RETRIBUSI PASAR SEBAGAI UPAYA PENINGKATAN PENDAPATAN ASLI DAERAH KOTA YOGYAKARTA - Yanendra Yanendra (Jurnal Kajian Akuntansi, 2009)
This examination have aim to know potention of market retribution, potention of market retribution, efficiency, effectiveness, contribution of retribution market for regional retribution and contribution of retribution for PAD. Data used secondary data that realisation of absorbtion and publication, valuation and receive realisation market retribution and the money collected cost market retribution for Dinas Pendapatan Asli Daerah dan Kerjasama Setda Yogyakarta, Dinas Pengelolaan Pasar Kota Yogyakarta, and Biro Pusat Statistik. Result of examination show that potention of market retribution in examination period 2004-2008 every year get to step on, and projection of market potention that 2009-2014 also every year to step on, appertain efficien and effectiveness, but contribution of market retribution for regional retribution and PAD inclined decrease. Key words: potention of market retribution, projection potention of market retribution, efficiency, effectiveness, and contribution of market retribution regional and to with respect to PAD. Key word: potention of market retribution, PAD